Digitalization and Tradition in Teaching Russian language (Proceedings of Southern Federal University. Philology, 2020)
The spread of digital technologies and their introduction into the sphere of education inevitably actualizes the methodological and methodological aspects of the methodology of teaching Russian as an independent field of scientific knowledge, as well as the problems of teaching the native language in a modern school and a modern lesson. In this regard, special consideration should be given to the meaning of traditional, «verbal education» and digital, distance learning for the development of the student’s personality and the development of his «gift of speech». The problem is analyzed taking into account the data of related Sciences that study a person and his speech abilities. Analysis of theoretical sources from philosophy, didactics, theory of speech activity, psychology, methods and Informatization of education leads to the conclusion that it is necessary to preserve verbal learning, due to the fact that communication is a trigger for the transformation of a natural person into a person of culture. The article considers the negative impact of the unregulated use of ICT resources in teaching Russian on the health, intellectual and emotional sphere of the student. In the process ofanalyzing the problem, it is concluded that it is necessary to include electronic resources in the process of teaching the native language, without exaggerating the role of technical teaching tools and belittling the role of the word and the function of the teacher.Key words: language, personality, development, teacher, communication, e-school, digitalization.DOI 10.18522/1995-0640-2020-3-197-204